Shallow-water hard corals (Hexacorallia: Scleractinia) from Bangka Belitung Islands Waters, Indonesia - Singgih A. Putra; Helmy Akbar; Indra A. Syari (Aceh Journal of Animal Science, 2019)
Bangka Belitung Islands (Sumatra, Indonesia) has various coastal resources, e.g., coral reefs, seagrass beds, mangrove forests. However, the coral community has been threatened by anthropogenic activities, i.e., tin mining and illegal tin mining. Threatened species assessment is important for mitigation of coral losses and management. The ojective of the present study was to examine the status of Scleractinian corals in Bangka Belitung Islands, Indonesia. A line intercept transect was performed for the coral reef survey. Live and dead coral cover were recorded in the three locations. Corals species were identified following taxonomic revisions. The results showed that there were 142 species of Scleractinian corals recorded from Bangka Belitung Islands. Of these, 22 species are the new report from the areas of the the eastern part of Belitung Island. Family of Merulinidae, Acroporidae, and Poritidae were predominant group in this region. It is concluded that the condition of the coral reef ecosystem in the Belitung Islands is relatively good, but fair in Gaspar Strait and Bangka Island.  Keywords: Coral cover, coral diversity, hard coral, Scleractinia